ISSUES OF INTRODUCING INNOVATION TO SMALL BUSINESSES - Adaxamov Xusniddin Akmaljon ugli; Rashidov Rahmatullo Alojonovich (International Journal of Artificial Intelligence for Digital Marketing, 2025)
Objective: This study examines the economic implications of adopting innovative technologies in small business manufacturing settings compared to traditional methods. Method: A systematic comparative analysis was conducted by evaluating key economic indicators—including productivity, cost efficiency, and profitability—across a sample of small business entities producing tangible products, with data gathered through quantitative methodologies and supported by case studies. Results: Findings reveal that businesses integrating innovative technologies experience significant improvements in operational efficiency and competitive positioning, demonstrating enhanced financial performance relative to those employing conventional practices. Novelty: The research contributes novel insights by identifying critical factors that drive the successful implementation of innovative strategies within small enterprises and by proposing tailored recommendations for optimizing technology adoption. These insights provide a framework for understanding the interplay between technological innovation and economic performance in small business contexts, offering a valuable basis for future studies and policy development aimed at fostering sustainable growth and resilience in the sector.